PENGEMBANGAN BAHAN AJAR BERBANTUAN E-FLASHCARD PADA SUBTEMA KEKAYAAN SUMBER ENERGI DI INDONESIA - Dita Anistia Wahyu; Sandi Budiana; Yuli Mulyawati (STKIP Subang, 2024)
ABSTRACT Dita Anistia Wahyu. 037120043. This study aims to develop and determine the feasibility of teaching materials assisted by e-flashcards on the subtheme of the wealth of energy sources in Indonesia in class IV SD Negeri Palalangon. The method in this study uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). This research involved one lecturer each of media experts, linguists, and material experts, and involved one teacher. The subjects in this study were fourth grade teachers and fourth grade students at SD Negeri Palalangon, Bogor Regency in the academic year 2023/2024 with a total of 25 students. From the results of the study it can be concluded that teaching materials assisted by e-flashcards are very feasible to use in learning. This is based on the results of validation conducted by validators obtained the final results of validation of media experts by 88%, language experts by 97%, lecturer material experts by 93,4% and teacher material experts by 91,7% which is included in the “Very Feasible” criteria. As well as based on the results of the student response questionnaire which obtained a result of 88% and the teacher who obtained a result of 94%, both of which were classified as “Very Good” criteria applied in learning. Keywords: Teaching Materials, E-Flashcards, Energy Source Wealth ABSTRAK Dita Anistia Wahyu. 037120043. Penelitian ini bertujuan untuk mengembangkan dan mengetahuikelayakan bahan ajar berbantuan e-flashcard pada subtema kekayaan sumber energi di Indonesia di kelas IV SD Negeri Palalangon. Metode dalampenelitian ini menggunakan metode Research and Development (R&D) dengan model pengembanganADDIE (Analysis, Design, Development, Implementation, Evaluation). Penelitian ini melibatkanmasing-masing satu orang dosen ahli media, ahlibahasa, dan ahli materi, serta melibatkan satu orang guru. Subyek pada penelitian ini adalah guru kelas IV dan peserta didik kelas IV di SD Negeri PalalangonKabupaten Bogor tahun akademik 2023/2024 denganjumlah 25 peserta didik. Dari hasil penelitian dapatdisimpulkan bahwa bahan ajar berbantuan e-flashcardsangat layak digunakan dalam pembelajaran. Hal ini berdasarkan hasil validasi yang dilakukan oleh validator diperoleh hasil akhir validasi ahli media sebesar 88%, ahli bahasa sebesar 97%, ahli materidosen sebesar 93,4% dan ahli materi guru sebesar91,7% termasuk pada kriteria “Sangat Layak”. Serta berdasarkan hasil kuesioner respon peserta didik yang memperoleh hasil sebesar 88% dan guru yang memperoleh hasil sebesar 94%, yang keduanyatergolong kriteria “Sangat Baik” diterapkan dalampembelajaran. Kata Kunci: Bahan Ajar, E-Flashcard, KekayaanSumber Energi